Design of an embedded system for the control and regulation of the dynamic process of charging and discharging of electrochemical cells and its subsequent validation for 1U CubeSat satellites - Gómez-Villagra, Kevin (2024)
Power conversion interfaces have evolved over time to optimize systems and obtain energy savings in many industries, including aerospace. The electrical power system (EPS) has been the most common failure in space missions, so a test platform for electrochemical cells was designed to prevent future failures. This project created a platform that includes digital current and voltage controllers, implemented with a software-based PID compensator designed with MATLAB and Simulink. The compensator was programmed on a PIC to control the power conversion interface. Finally, the PCB and a 3D representation of the silver-form were developed to test electrochemical cells and validate their operation.